Influence Of Earnings Per Share (Eps) And Return On Equity (Roe) On Share Prices In Manufacturing Companies Of The Consumer Goods Industry Listed On The Indonesian Stock Exchange - Syafira Mariana (Journal of Business, Accounting and Finance, 2023)
The purpose of this study is to determine: 1) The effect of EPS (Earnings Per Share) on the share prices of consumer goods manufacturing companies listed in the BEI. 2) The effect of Return On Equity (ROE) on the share prices of consumer goods industry manufacturing companies listed in the BEI. 3) The effect of Earnings Per Share (EPS) and Return On Equity (ROE) on the share prices of consumer goods industry manufacturing companies listed in the BEI. The population in the study included 40 consumer goods industry enterprises from 2017 to 2022. With a sample number of 5 companies were selected using the purposive sampling method. The methods used in this study are the descriptive method and the verifiative method. The results of the study showed that EPS (Earnings Per Share) has a significant effect on the share price of manufacturing companies in the consumer goods industry sector listed on the Indonesian stock exchange. ROE (Return On Equity) has no significant effect on the share prices of manufacturing companies of the consumer goods industry sector listed in the BEI. Simultaneously, both the variables Earnings Per Share (EPS) and Return On Equity (ROE) together have a significant effect on the share prices of the consumer goods industry manufacturing companies listed in the BEI.